IMMUNOSTIMULATORY EFFECT OF VITAMIN C ON MICE INDUCED BY STAPHYLOCOCCUS AUREUS - Khairani, Iffa Afiqa; Riana, Elisa Nurma; Maretta, Gres; Azizah, Najla Nur; Putri, Isnaini Anggraini; Maruli, Berkat Afni; Mulyadi, Salsa Pratiwi; Antonius, Antonius (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2023)
Several compounds that can boost immune activity (immunostimulatory) include vitamin E, curcumin, flavonoids, and vitamin C. In this study, ascorbic acid or vitamin C, was used as one method to enhance the immune system. This study aims to determine the immunostimulatory effect of vitamin C on the phagocytosis activity of macrophages in mice induced by Staphylococcus aureus. The mice were divided into two groups: the control group, which received 0.3 ml of distilled water orally, and the treatment group, which received 0.036 mg/g BW of vitamin C orally for 14 days. On the 15th day, each mouse was intraperitoneally induced with 0.5 mL of Staphylococcus aureus bacterial suspension and left for two hours. The phagocytic activity value represents the percentage of active macrophage cells among all macrophages observed. The result showed that the value of % phagocytic activity in the control group was 21.43% ± 7.92, whereas the % phagocytic activity in the treatment group was 48.31% ± 22.27. The group of mice given vitamin C 0.036 mg/g BW orally showed increased phagocytic activity compared to the control group mice. This shows that vitamin C has potential as an immunostimulator.